Oscillation of certain fourth-order functional differential equations - Agarwal, P.; Grace, S. R.; O’Regan, D. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Some new criteria for the oscillation of fourth-order nonlinear functional differential equations of the form$$\frac{d^2}{dt^2} \left(a(t) \left(\frac{d^2x(t)}{dt^2}\right)^{α} \right) + q(t)f(x[g(t)])=0, \quad α>0,$$are established.